MENINGKATKAN KEMAMPUAN BERBICARA SISWA MELALUI METODE SHOW AND TELL DI SEKOLAH DASAR - Muhammad Nur Abdillah; Erni Mariana; Nurkaif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Speaking skills are essential language competencies that must be developed at the elementary school level because they support students’ ability to express ideas and communicate orally. Preliminary observations in the third grade of SD Negeri 2 Sanggar Buana showed that students’ speaking skills were still low, particularly in pronunciation, intonation, word accuracy, sentence organization, and fluency. This study aimed to improve students’ speaking skills through the implementation of the Show and Tell method. This research employed Classroom Action Research conducted in two cycles involving 12 third-grade students. Data were collected through observation using a speaking skills assessment rubric and analyzed using descriptive quantitative analysis. The results showed that students’ speaking mastery increased from 25% in Cycle I to 89% in Cycle II. Improvements occurred across all speaking indicators. Therefore, the Show and Tell method is effective in improving elementary school students’ speaking skills.